If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -15 = 6(x + -5) Reorder the terms: -15 + 9x = 6(x + -5) Reorder the terms: -15 + 9x = 6(-5 + x) -15 + 9x = (-5 * 6 + x * 6) -15 + 9x = (-30 + 6x) Solving -15 + 9x = -30 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. -15 + 9x + -6x = -30 + 6x + -6x Combine like terms: 9x + -6x = 3x -15 + 3x = -30 + 6x + -6x Combine like terms: 6x + -6x = 0 -15 + 3x = -30 + 0 -15 + 3x = -30 Add '15' to each side of the equation. -15 + 15 + 3x = -30 + 15 Combine like terms: -15 + 15 = 0 0 + 3x = -30 + 15 3x = -30 + 15 Combine like terms: -30 + 15 = -15 3x = -15 Divide each side by '3'. x = -5 Simplifying x = -5
| 124-42= | | 5-4j-2=-5j+7 | | 10+7-3n+2=7n-1 | | 0.166667d+0.166667=0.25(d-2) | | -2m+1=17 | | 48+96x-16x^2=47 | | 2(x+3)+4(3x-6)= | | -1x+6=2-x-15 | | (3a^4b)-(3a^2b^4)= | | 1/2(x)=10/6 | | -7n=-6n+6 | | 30x-32x= | | 78=x+2y | | 5x+9+2x+13=90 | | (-84)+(-41)= | | -4-n=-3n+n | | b=65+(15+9)w | | -q+10=-6-3q | | Cosx+2*sinx*tanx=1 | | 6(6x-2)=-228 | | 2(-2)-y=4 | | 4t(t+5)= | | -3x+8+4x=4+x+4 | | -8z=-5-9z | | v-8=5v+8 | | -9(1+7b)=-32 | | 9-4x-6-6x=5 | | 12x-9=5x+40 | | 3x-5(x-5)=-6+5x-11 | | -7+4(7b-2)=209 | | 10-20=-b | | 2r-3.1=1.17 |